2021
DOI: 10.21037/tau-21-559
|View full text |Cite
|
Sign up to set email alerts
|

Case selection and implementation of tubeless percutaneous nephrolithotomy

Abstract: Background: The tubeless percutaneous nephrolithotomy (PCNL) was proposed to eliminate the side effects of the nephrostomy tube in recent years, such as pain, channel infection, postoperative bleeding, and longer hospital stay. But there is neither clinical guidelines nor consensus about tubeless PCNL in clinical practice. The study is aimed to how to implement the tubeless PCNL step by step, including case selection preoperatively, improving the technique of the surgeon, making the correct decisions at the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Numerous studies have demonstrated that the tubeless PCNL (ureteral stent only) technique is being employed with increasing frequency. It has been reported to be both safe and effective, as well as associated with a shorter hospital stay and a reduced incidence of postoperative pain [ 6 , 22 , 23 ]. Nevertheless, completely tubeless PCNL technique (neither ureteral stent nor nephrostomy tube) is still challenging and must also be performed by experienced surgeons [ 7 , 24 – 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that the tubeless PCNL (ureteral stent only) technique is being employed with increasing frequency. It has been reported to be both safe and effective, as well as associated with a shorter hospital stay and a reduced incidence of postoperative pain [ 6 , 22 , 23 ]. Nevertheless, completely tubeless PCNL technique (neither ureteral stent nor nephrostomy tube) is still challenging and must also be performed by experienced surgeons [ 7 , 24 – 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Related studies have shown that tubeless PCNL has been proven to be the safest and most effective compared to standard and totally tubeless PCNL [ 25 ]. Due to the absence of an indwelling nephrostomy tube, the VAS pain score in tubeless PCNL group was significantly lower than that in PCNL group [ 26 ]. It is also consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Xun et al [ 27 ] has demonstrated that tubeless PCNL was a feasible and effective choice for strictly selected patients, and its advantages include low postoperative pain, short postoperative hospitalization, and quick recovery. [ 28 ] For patients undergoing LIA, tubeless PCNL is suitable because of these advantages; however, these patients must be selected strictly. The criteria for tubeless PCNL under LIA in our study were similar to those used under general anesthesia, [ 7 ] and 10 patients underwent tubeless MPCNL in our study.…”
Section: Discussionmentioning
confidence: 99%